Bem-estar financeiro: proposição e validação de uma medida de percepção - Matheis, Taiane Keila (2022)
Financial well-being is a multifaceted concept that to date does not have a single scale to measure it (BASHIR; QURESHI, 2022; BRÜGGEN et al., 2017). Because Brazil has a heterogeneous economy and is a developing country that has a high level of indebtedness, it is healthy to seek a measure to understand the level of financial well-being of Brazilians. As financial well-being is one of the dimensions of general well-being, the existence of an adequate measure of financial well-being is essential to assess public strategies and policies that aim to improve the well-being of the population. Thus, the present work sought to create and validate a scale to measure perceived financial well-being. To achieve the proposed objective, 3,313 questionnaires were applied in ninety-four cities in the five Brazilian geographic regions. The construction of the scale took place in two stages: qualitative and quantitative. In the qualitative stage, sixteen individuals participated in interviews about the perception of financial well-being. Soon after, the initial instrument was validated by six experts and a pre-test was carried out with ten individuals from different socioeconomic and demographic profiles, aiming to identify the degree of pertinence, relevance, adequacy and understanding of the items and dimensions of the scale, resulting in thirty and four items. In the quantitative stage, the items, dimensions and model were validated by exploratory and confirmatory factor analysis. It was necessary to improve the model, with the removal of some items and the insertion of correlation between errors. The final model of the Perceived Financial Well-Being Scale (PFWBS) is composed of twenty-three items distributed in four dimensions: financial security, financial tranquility, financial freedom and satisfaction with financial management. A methodology for the application of the Perceived Financial Wellbeing Scale (PFWBS) is also being proposed, ranging from one to five, the closer to five, the higher the level of perceived financial well-being. This measure presented satisfactory evidence and psychometric tests, and can be reproduced in future studies in emerging countries. In Brazil, the perceived level of perceived financial well-being is low. Significant part of the sample: women, young people, blacks and browns, with low education and income are those who significantly contributed to this result. Thus, the PFWBS can be useful in evaluating the results of different public policies, such as income transfer and financial education programs.